Amazing stories of the space age : true tales of Nazis in orbit, soldiers on the moon, orphaned martian robots, and other fascinating accounts from the annals of spaceflight - Pyle, Rod (Prometheus Books, 2017)
Reveals the most unusual space missions ever devised inside and outside of NASA during a time when nothing was too odd to be taken seriously, and the race to the moon and the threat from the Soviet Union trumped all other considerations. --Publisher.